Taming Japan's deflation : the debate over unconventional monetary policy - Park, Gene, 1971-; Katada, Saori N.; Chiozza, Giacomo; Kojo, Yoshiko, 1956- (Ithaca : Cornell University Press, 2018)
"Discusses how entrenched monetary policy ideas within the Bank of Japan, protected by policy network, inhibited addressing persistent deflation since its de jure independence of 1998"--
Ideas, networks and monetary politics in Japan -- Deflation, monetary policy responses, and the BOJ -- Monetary politics: interests, ideas and policy networks -- The BOJ worldview and its historical development -- The monetary policy network -- Ideas and monetary policy: a quantitative test -- Monetary policy making 1998-2012 -- Abenomics and the break with the BOJ orthodoxy.
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Nihon Ginkō; Monetary policy -- Japan; Deflation (Finance) -- Japan; Banks and banking, Central -- Japan; Japan -- Economic policy -- 1989-